Physiologic Evaluation of Ventilation Perfusion Mismatch and Respiratory Mechanics at Different Positive End-expiratory Pressure in Patients Undergoing Protective One-lung Ventilation. (March 2018) - Spadaro, Savino; Grasso, Salvatore; Karbing, Dan Stieper; Fogagnolo, Alberto; Contoli, Marco; Bollini, Giacomo; Ragazzi, Riccardo; Cinnella, Gilda; Verri, Marco; Cavallesco, Narciso Giorgio; Rees, Stephen Edward; Volta, Carlo Alberto
Abstract : Background: Arterial oxygenation is often impaired during one-lung ventilation, due to both pulmonary shunt and atelectasis. The use of low tidal volume (VT ) (5 ml/kg predicted body weight) in the context of a lung-protective approach exacerbates atelectasis. This study sought to determine the combined physiologic effects of positive end-expiratory pressure and low VT during one-lung ventilation. Methods: Data from 41 patients studied during general anesthesia for thoracic surgery were collected and analyzed. Shunt fraction, high V/Q and respiratory mechanics were measured at positive end-expiratory pressure 0 cm H2 O during bilateral lung ventilation and one-lung ventilation and, subsequently, during one-lung ventilation at 5 or 10 cm H2 O of positive end-expiratory pressure. Shunt fraction and high V/Q were measured using variation of inspired oxygen fraction and measurement of respiratory gas concentration and arterial blood gas. The level of positive end-expiratory pressure was applied in random order and maintained for 15 min before measurements. Results: During one-lung ventilation, increasing positive end-expiratory pressure from 0 cm H2 O to 5 cm H2 O and 10 cm H2 O resulted in a shunt fraction decrease of 5% (0 to 11) and 11% (5 to 16), respectively ( P < 0.001). The PaO2 /FIO2 ratio increased significantly only at a positive end-expiratory pressure of 10 cm H2 O ( P < 0.001). Driving pressure decreased from 16 ± 3 cm H2 O at a positive end-expiratory pressure of 0 cm H2 O to 12 ± 3 cm H2 O at a positive end-expiratory pressure of 10 cm H2 O ( P < 0.001). The high V/Q ratio did not change. Conclusions: During low VT one-lung ventilation, high positive end-expiratory pressure levels improve pulmonary function without increasing high V/Q and reduce driving pressure. Abstract : Shunt fraction and ventilation/perfusion ratio V/Q distribution was measured in 41 patients undergoing one-lung anesthesia. Positive end-expiratory pressure at 5 or 10 cm H2 O, applied in random order, resulted in lower shunt fraction and driving pressure, without increasing dead space.Supplemental Digital Content is available in the text.